RESPONSE OF ASIAN COUNTRIES TO THE WIDESPREAD OF DUAL CITIZENSHIP POLICIES - HILAL RAMDHANI (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2024)
Citizens are an element of the existence of a country, so that citizens are an important factor in the sustainability of a country. In the modern era, where people have high mobility to travel and even live abroad, marriages from different countries are increasingly massive, which encourages the birth of children from parents from different countries. This condition gives rise to various challenges in determining the legal status of citizenship, one of which is giving rise to political decisions to recognize dual citizenship. Politically, dual citizenship is a very dilemmatic political decision for Asian countries which have historically experienced a period of colonialism, economic activities that are still dependent on the West, and strong nationalism, making the political decision to implement dual citizenship variously contradictory. The aim of this research is to reveal the response of countries in Asia to the widespread political decisions regarding dual citizenship. This article uses literature studies sourced from various studies related to dual citizenship, especially in Asian countries. The research results show that it is more difficult for countries in Asia to accept dual citizenship due to historical, economic and nationalistic aspects, as well as other aspects that show differences with countries in Europe, America and Africa. Countries in Asia have not fully responded well to the spread of dual citizenship, so dual citizenship is still an issue that is fought for by the diaspora and faces opposition from local communities.